The Role of Songs in English Language Teaching (ELT): An Introduction to Musical Pedagogy - Nikita Gadani (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2015)
“If learners are interested, education happens” aptly espoused by Sugata Mitra. Taking from his notion of entertainment, one loves to bank on the idea and take it up to the classroom. What can be more entertaining and engaging than music! Everyone enjoy music while travelling, at home, studying or even at work place. Rather than telling students to put off their smart phones, why not to make them pedagogical tools. It is in this context that the paper proposes using songs to teach English. Teacher can use song to start and end up their sessions, to illustrate theme, to teach grammar, vocabulary and sentence structure. It also helps in learning and memorizing of linguistic structures. Undoubtedly, listening reinforces proficiency in English among second language learners. The paper focuses on how songs can be used as a valuable part of language teaching curriculum and help learners to improve their pronunciation. Besides, the peculiar melody of English language is difficult to teach in a second language learning environment. It is here that songs play great role in training students’ ears to that melody. The paper also focuses on how songs reflect culture and increase students’ overall understanding of socio- cultural background of English Language and that too with enjoyment in the classroom.